Is It Me or Her? How Gender Composition Evokes Interpersonally Sensitive Behavior on Collaborative Cross-Boundary Projects - Williams, Michele; Polman, Evan (Organization Science, 2015)
This paper investigates how professional workers’ willingness to act with interpersonal sensitivity is influenced by the gender and power of their interaction partners. We call into question the idea that mixed-gender interactions involve more interpersonal sensitivity than all-male interactions primarily because women demonstrate more interpersonal sensitivity than do men. Rather, we argue that the social category “women” can evoke more sensitive behavior from others such that men as well as women contribute to an increase in sensitivity in mixed-gender interactions. We further argue that the presence of women may trigger increased sensitivity such that men can also be the recipients of more sensitivity when one or more women are present on a team. In a study of 202 management consultants, we found that the willingness to act with interpersonal sensitivity increased in interactions with women. Moreover, this effect was greater in interactions with women who had low reward power—i.e., females who better fit the expectations associated with the social category “women.” We also found team-level effects. Professionals working with mixed-gender versus all-male client teams reported a greater willingness to act with interpersonally sensitive behavior toward male client team members. Our findings show that the willingness to act with interpersonal sensitivity is context dependent and shed light on the importance of studying interaction partner-level and team-level effects on willingness to act with interpersonal sensitivity.